Time-consistent monetary policy, terms of trade manipulation and welfare in open economies - Sebastian Schmidt (European Central Bank (ECB), 2018)
A key insight from the open economy literature is that domestic price stability is in general not optimal for countries that exert some market power over their terms of trade. Under commitment, a national benevolent monetary policymaker improves upon the allocation associated with stable domestic prices by manipulating the terms of trade to her own country's advantage. In this paper, I study optimal monetary policy in a sticky-price small open economy model when the policymaker lacks a commitment device. Without commitment, the benevolent policymaker's attempt to improve national welfare by manipulating the terms of trade can be self-defeating. By steering international relative prices the discretionary policymaker induces fluctuations in domestic prices, the costs of which she is unable to fully internalize in her decision-making. Society may thus be better off if it appoints an inward-looking policymaker who aims for domestic price stability and resists the temptation to exploit the country's monopoly power in trade. Accounting for the effective lower bound on nominal interest rates further strengthens the case for the inward-looking policy objective.
Keywords: E52; F41; 330; small open economy; optimal monetary policy; discretion; delegation; terms of trade externality